Ballistic study on the penetration potential and injury potential of different bullet types in the use of a newly developed bullet shooting stunner for adequate stunning of heavy cattle - Gascho, Dominic; Stephan, Roger; Zoelch, Niklaus; Vogt, Michael; Oesch, Michelle Aimée; Thali, Michael; Richter, Henning (Frontiers in Veterinary Science, 2023)
A dedicated bullet shooting stunner for heavy cattle was recently developed, which resemble the handling of a normal captive bolt gun, but fire a bullet instead of the bolt feed. In the search for a suitable ammunition, the following criteria must be met: First, the energy of the bullet must be sufficient to penetrate the thick frontal bones of heavy cattle. Second, the injury potential at the corresponding penetration depth should preferably be large in order to damage brain tissue relevant to stunning. Third, the bullet must not perforate the occipital bone (over-penetrate). In this ballistic study, four different bullet types (Hornady FTX, Hydra-Shok, Black Mamba, and a common full metal jacket (FMJ) bullet) were evaluated in a series of experiments on soap blocks and removed bone plates followed by computed tomography examinations. Penetration potential was evaluated in terms of kinetic energy relative to the caliber of the bullet, i.e., energy density. The energy densities (ED) of all four bullet types were sufficient to penetrate the frontal bone (Hornady FTX: ED=17.50 J/mm2, Hydra-Shok: ED=17.46 J/mm2, Black Mamba: ED=13.47 J/mm2, FMJ: ED=13.47 J/mm2). The Hornady FTX and the Hydra-Shok each fragmented heavily. Only the FMJ over-penetrated and was excluded after three experiments. Injury potential was evaluated by the mean extent of the cavity volume (eCV) at the relevant penetration depth of 5.5 to 7.5 cm in the soap block (Hornady FTX: eCV=3.77 cm2, Hydra-Shok: eCV=2.71 cm2, Black Mamba: eCV=1.31 cm2). For use in heavy cattle, the Hornady FTX and the Hydra-Shok are recommended due to the significantly (p=0.006) and considerably larger eCV than the Black Mamba.